2015
DOI: 10.4238/2015.september.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and genetic structure of consecutive breeding generations of golden mandarin fish (Siniperca scherzeri Steindachner) using microsatellite markers

Abstract: ABSTRACT. In this study, 12 polymorphic microsatellites were investigated to determine the genetic diversity and structure of 5 consecutive selected populations of golden mandarin fish (Siniperca scherzeri Steindachner). The total numbers of alleles, average heterozyosity, and average polymorphism information content showed that the genetic diversity of these breeding populations was decreasing. Additionally, and SC101-222 bp changed regularly in the 5 breeding generations. Their frequencies were gradually inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, to confirm this relationship, further association analysis studies between traits are necessary. Luo et al (2015), reported that selection in breeding program causes genes in populations to become homozygous; the affected genes are typically associated with a trait of fish species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to confirm this relationship, further association analysis studies between traits are necessary. Luo et al (2015), reported that selection in breeding program causes genes in populations to become homozygous; the affected genes are typically associated with a trait of fish species.…”
Section: Resultsmentioning
confidence: 99%
“…Number of studies have been using microsatellite markers to conduct genetic monitoring in selective breeding lines, such as Siniperca scherzeri (Luo et al, 2015), Ruditapes philippinarum (Yu et al, 2011), andPseudosciaena crocea (Hao et al, 2010). Nevertheless, few information about genetic structure of striped catfish populations thought breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…As time under selection increased, the genetic diversity tended to reduce, the differentiation between generations became less, and the variation of genetic structure of the populations became smaller. Luo et al (2015) studied the genetic diversity and structure of 5 consecutive selected populations of golden mandarin fish (Siniperca scherzeri Steindachner) with microsatellite markers and observed reduced genetic diversity over generations and there was increased genetic distance between adjacent generations. They opined that the generation populations of breeding had not fully adopted to the existing selection pressure and environment, and thus the population genetic structure had not yet stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have revealed that consecutive breeding for many generations has led to decreased genetic diversity in golden mandarin fish (Siniperca scherzeri Steindachner) as revealed by microsatellite markers 1. (Luo et al, 2015). Likewise, artificial selection is likely to have imposed distinctive signatures on Atlantic salmon (Salmo salar) characterized by reduction in genetic diversity and high genetic differentiation from other populations (Lopez et al, 2019).…”
Section: Effects Of Artificial Selection On Low Genetic Diversity Of Rymentioning
confidence: 99%